Walsh, Daphne. New Perlican Photograph of a man, woman, and child in front of a tree. - Barrett, Terra (1945)
A photograph of William Hobbs (left), Leah (Warren) Hobbs (right), and Raymond (centre) at four years old in 1945. Above the photo says "Family Memories." The photograph was printed by Kodak.